Cadar dan Tradisi Diskursif "Taat" bagi Perempuan Muslim Indonesia - Wahyudi Akmaliah (Studia Islamika, 2023)
Eva F. Nisa. 2023. Face-Veiled Women in Contemporary Indonesia. London and New York: RoutledgeMost studies of face-veiled Muslim women are placed in the stereotype discourse; a part of subordination or terrorist group affiliation. Many scholars also argue that those women’s bodies are exploited under the patriarchal structure and its religious interpretation with the dominant male’s perspective. Eva F. Nisa in this book has proposed a different perspective, employing ethnographic research and taking a case study of two women communities of Islamic revivalist backgrounds (Jamaah Tabligh and Salafi Movement) in Indonesia. Throughout developing from Saba Mahmood’s theory of the politic of piety mostly, Nisa found that the Islamic lifestyle is the firm argument among the cadari, in which they practice the term of taat, which is part of a discursive tradition in Islam, to strengthen their path in the true path of Islam.